2014
DOI: 10.1063/1.4893668
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of fermi-level pinning effect at metal/germanium interface by the insertion of graphene layers

Abstract: In this paper, we report the alleviation of the Fermi-level pinning on metal/n-germanium (Ge) contact by the insertion of multiple layers of single-layer graphene (SLG) at the metal/n-Ge interface. A decrease in the Schottky barrier height with an increase in the number of inserted SLG layers was observed, which supports the contention that Fermi-level pinning at metal/n-Ge contact originates from the metal-induced gap states at the metal/n-Ge interface. The modulation of Schottky barrier height by varying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…The Ge/Co Schottky barrier could be tuned by the number of layers of the inserted graphene. Graphene here has potential as the tunneling barrier for spin injection from Co to Ge …”
Section: Graphene Contact To Conventional Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ge/Co Schottky barrier could be tuned by the number of layers of the inserted graphene. Graphene here has potential as the tunneling barrier for spin injection from Co to Ge …”
Section: Graphene Contact To Conventional Semiconductorsmentioning
confidence: 99%
“…Graphene here has potential as the tunneling barrier for spin injection from Co to Ge. 114 Gallium Nitride. As a wide band gap (3.4 eV) semiconductor, GaN has been widely used in bright light-emitting diodes (LEDs).…”
Section: Graphene Contact To Conventional Semiconductorsmentioning
confidence: 99%
“…The scalable integration of graphene onto semiconductor platforms is an important step toward utilizing the exceptional structural, electronic, thermal, and mechanical properties of graphene in conventional semiconductor technologies. In particular, graphene/Ge heterostructures have emerged as an exciting materials system for state-of-the-art electronics for several reasons: (1) graphene supported on Ge can simultaneously exhibit high charge carrier mobility and concentration; 1 (2) hybrid photodetectors based on graphene/Ge Schottky barrier junctions can exhibit high responsivity; 2,3 (3) the insertion of graphene between metals and Ge can alleviate Fermi-level pinning to improve contact resistance; 4 (4) the insertion of graphene between dielectrics and Ge can suppress formation of interfacial defect states to reduce hysteresis and leakage current in Ge-based devices; 5 (5) graphene can decouple interlayer bonding to grow nonlatticematched III−V semiconductors directly on Ge; 6 and (6) chemical templates consisting of alternating stripes of graphene and Ge can direct the assembly of block copolymers into nanoscale patterns. 7 These applications, however, are sensitive to the structural, electronic, and chemical nature of the graphene/Ge interface.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, since the interface layer resistance is added, the direct metal=Ge interface with a low SBH is more preferable from the viewpoint of contact resistance reduction. With respect to the direct metal=Ge interface, it has recently been reported that the SBHs at epitaxial Fe 3 Si, 18) α-TiGeN, 19) epitaxial Mn 5 Ge 3 , 20) epitaxial NiGe 2 , 21) graphene, 22) and Sn 23) =n-Ge interfaces are relatively low, which deviates from the trend of strong FLP. 7,8) Some of them 18,20,21,23) considered that the FLP on Ge might not be determined by an intrinsic but extrinsic origin.…”
mentioning
confidence: 95%